Flynn effect: Generation growth of IQ - Igor Vujović; Djordje Petronić (Биомедицинска истраживања, 2020)
In the 1980-s, the attention of the public was attracted by the research of James Flynn, who noticed something interesting - as the time went by, respondents achieved higher scores in the IQ tests. According to his research, as well as the researches of the authors who were engaged in the subject, the observed increase was 4.4 points per decade on average. These increases varied across different environments, however, in almost every country where research was conducted the point increases in IQ tests were observed. In addition to the observed increases in the IQ tests, it was also necessary to uncover the reasons for such results. The aim of the study is to present the results of the empirical research confirming this phenomenon, as well as to provide some possible explanations related to its occurrance. The relevant literature have singled out education, test exposure, nutrition and health care, reduction in the number of primary family members and heterosis as the possible reasons for the above-mentioned point increases.
Keywords: Flynn effect; intelligence; increase in IQ; neurophychological assessment